A situational analysis of model holistic-comprehensive and integrated approaches to handling stunting in Buleleng Regency, Bali, Indonesia - Setiawan, Komang Hendra; Hartono, Made Sugi; Budiarta, I Wayan; Wirabrata, Dewa Gede Firstia; Sekarini, Ni Nyoman Ayu Desy (MEDISAINS: Jurnal Ilmiah Ilmu-Ilmu Kesehatan, 2024)
Background: Policies and strategies for handling stunting cases effectively and efficiently vary in different regions, depending on their situation and conditions. There has yet to be an empirical study of stunting management with a holistic-comprehensive and integrated approach in Indonesia, especially in Buleleng Regency, Bali. Thus, conducting initial research to analyze the policy and determine the right stunting management strategy to implement is essential. Purpose: This study aims to map stunting cases, explore their causal factors, analyze the suitable policy model for overcoming stunting and describe the effective and efficient stunting management strategy in Buleleng Regency based on a holistic, comprehensive, and integrated approach. Methods: This is a situation analysis case study. Respondents were stunted children and related governmental agencies in Buleleng Regency, Bali. The incidence of stunting, risk factors suspected as the cause, policy models and appropriate stunting handling strategies were analyzed in depth using qualitative and quantitative methods. Results: There were 1040 cases of stunting in the regency, with the highest cases in Banjar District. Significant risk factors influencing the stunting incidence in the region include the lack of good complementary feeding (OR: 2.6722; p <0.05) and low family income (OR: 7.6667; p <0.0001). The results of the analysis of stunting handling policies, based on a holistic-comprehensive and integrated approach model by regional needs, are categorized into two policy areas: Policies in the Medical and Non-Medical fields. In contrast, the handling strategy is divided into two stages: the screening and the handling stages. Conclusion: Poor-quality complementary foods and low family income are the main risk factors for high stunting rates in Buleleng Regency, Bali. These factors must be considered in an effective and efficient policy and strategy model for handling stunting cases in the regency.